PRARANCANGAN PABRIK ASAM OKSALAT DARI TETES DENGAN KAPASITAS 30.000 TON/TAHUN - , MUTIA AYUNI PRAKASITASARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Oxalic acid is organic compound which belongs to dicarboxilyc acid having miscellaneous function such as bleaching and cleaning agent, reagent in lantanide-based chemical industries,etc. The demand of oxalic acid is getting higher in accordance with the increasing growth of chemical industries. For this reason, this oxalic acid is planned to be built by utililizing 76,145 tons/year of mollases as main raw material. It will be operated by 2016 with 30,000 tons/year of oxalic acid production capacity. This plant will produce 58,758.52 tons/year of gypsum and 14.076,84 tons/year of Calsium Citrate as side products. The plant will be located in Central Lampung on a land area of 5.04 hectares with 242 employees. During its operation, it will need 53,872.5878 kg/hour of water, 75.6 m3/hour of instrument air, 158,962.50 kg/hour of dry air, 1,594.62 kg/hour of fuel, 5,753.71 kg/hour of steam, and 1,210.26 kW of electricity. From the results of economic evaluations, it can be summaried that: Fixed Capital Investment (FCI) is $ 20,482,154.73 + Rp 110,378,745,768.65